The Impact of Joseph Heller Post-Modernist Features in the Recent Scientific Studies - Neziri, Anita (Richtmann Publishing, 2013)
It is a crucial issue alongside other important topics to the academic level and also for the students who are interested in thisregard. After the Second World War there were some writers who possessed some characteristics that we may categorize onlyto that period. One of these writers is the famous American one Joseph Heller. There are many books about the war butHellerâ€™s masterpiece â€œCatch-22â€ is uncomparable to none of them. Heller is a satirical novelist, a short story writer and aplaywright.(a) The features that led to â€œBlack Humorâ€ .The humor that Heller makes use of is obviously a human selfishness invain, this is very well represented in almost all the characters of this novel. The humor is dressed up in these characters toexplain the absurdity even when they think that they are being moral and fair. (b)Humor as a stylistic choice. Joseph Heller isinterested in a non-chronological narration and has been focused in a repetitive style approach. Heller was not alone in the warnovels there many other such as Kurt Vonnegut ,or Thomas Pynchon etc